2007
DOI: 10.1007/s11274-007-9383-x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production from sweet sorghum juice in batch and fed-batch fermentations by Saccharomyces cerevisiae

Abstract: Sweet sorghum juice supplemented with 0.5% ammonium sulphate was used as a substrate for ethanol production by Saccharomyces cerevisiae TISTR 5048. In batch fermentation, kinetic parameters for ethanol production depended on initial cell and sugar concentrations. The optimum initial cell and sugar concentrations in the batch fermentation were 1 · 10 8 cells ml -1 and 24°Bx respectively. At these conditions, ethanol concentration produced (P), yield (Y ps ) and productivity (Q p ) were 100 g l -1 , 0.42 g g -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 10 publications
4
81
0
3
Order By: Relevance
“…The development of fermentation processes is one of the most important factors for efficient ethanol production [19][20][21][22]. In many distilleries, fermentation processes of ethanol production are conducted in single batch or continuous modes [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The development of fermentation processes is one of the most important factors for efficient ethanol production [19][20][21][22]. In many distilleries, fermentation processes of ethanol production are conducted in single batch or continuous modes [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Nuanpeng et al (2011) observed in a repeated-batch study that very high gravity (VHG) fermentation is a good alternative to produce high ethanol concentrations from sweet sorghum juice when an adequate level of yeast cell concentration, nitrogen, and agitation are used. On the other hand, Laopaiboon et al (2007) reported better results in fed-batch fermentation compared to batch configuration, in terms of ethanol concentration and product yield but not in productivity (measured as grams of ethanol generated/L/hr). These findings indicate the need to optimize parameters as feeding and withdrawn rate in order to optimize yields.…”
Section: Ethanol Fuel From Sweet Sorghum Juicementioning
confidence: 85%
“…Then, the supernatant was determined for residual total sugar and reducing sugar by phenol-sulfuric acid method (Mecozzi, 2005) and dinitrosalicylic acid (DNS) method (Bailey, 1988), respectively. Ethanol concentration (P) was analyzed by gas chromatography (Shimadzu GC-14B, Japan, solid phase: polyethylene glycol (PEG-20M), carrier gas (200 KPa): nitrogen, 150°C isothermal packed column, injection temperature 180°C, flame ionization detector temperature 250°C; gas chromatography (GC) solution analysis Version 2.30) and 2-propanol was used as an internal standard (modified from Laopaiboon et al, 2007). The ethanol yield (Yp/s) was calculated and expressed as g ethanol produced per g sugar utilized (g g -1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the development of new sweet sorghum cultivars with high grain and sugar yield (Almodares et al, 2007), fermentation process development is also important for efficient ethanol production from SSJ (Laopaiboon et al, 2007). In this study, we are interested in repeated-batch fermentation because this process has several advantages compared to conventional batch fermentation such as no new inoculum requirement for each batch (Bajpai and Bajpai,1988) and long-term productivity (Anastassiadis and Rehm 2006).…”
Section: Introductionmentioning
confidence: 99%